2013
DOI: 10.19030/cier.v7i1.8308
|View full text |Cite
|
Sign up to set email alerts
|

Effective Academic Advisory Committee Relationships

Abstract: Recently, accrediting bodies are placing great responsibility for accountability on universities and academic schools, departments, and programs. The goal of the increased accountability is improved quality of teaching and learning. In this paper, we describe several levels of accountability for quality teaching and learning in a small, private, liberal arts college. We describe the role the Universitys Board of Trustees. Moving to the School of Business Administration, we explain several activities the Board … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
1
0
1
Order By: Relevance
“…Kampus sebagai pemberi layanan pembelajaran yang bermakna, berupaya untuk penguatan kesiswaan, kewargaan global, menusia berpengetahuan dan berketerampilan (Bennett, Sunderland, Bartleet, & Power, 2016). Sebagai contoh di Universitas Marymount, Amerika Serikat, perwalian akademik sebagai sebuah tim atau panitia yang saling bekerja sama dengan unit akademik (Schaeffer & Rouse, 2013). Perwalian akademik atau penasehat akademik sebagai upaya untuk meningkatkan akuntabilitas pembelajaran.…”
Section: Hasil Dan Pembahasanunclassified
“…Kampus sebagai pemberi layanan pembelajaran yang bermakna, berupaya untuk penguatan kesiswaan, kewargaan global, menusia berpengetahuan dan berketerampilan (Bennett, Sunderland, Bartleet, & Power, 2016). Sebagai contoh di Universitas Marymount, Amerika Serikat, perwalian akademik sebagai sebuah tim atau panitia yang saling bekerja sama dengan unit akademik (Schaeffer & Rouse, 2013). Perwalian akademik atau penasehat akademik sebagai upaya untuk meningkatkan akuntabilitas pembelajaran.…”
Section: Hasil Dan Pembahasanunclassified
“…The implementation of such an endeavor requires buy-in from faculty and administration to incorporate student voice in the educational process. Schaeffer and Rouse (2014) found that a critical role of any advisory board is to limit an academic unit from operating in vacuum and thus being out of touch with students and the industry they intend to enter.…”
Section: Sport Management Student Advisory Board (Sm-sab)mentioning
confidence: 99%